Regime tributário diferenciado (rtd) do ICMS no Pará: um diagnóstico à luz da constituição financeira no contexto da guerra fiscal - MESQUITA, Patrick Bezerra (Universidade Federal do Pará, 2023)
This dissertation aims to clarify to what extent the tax benefits embodied in the ICMS Differentiated Tax Regime (RTD) in the State of Pará meet the legal requirements of the Financial Constitution and the Fiscal Responsibility Law in the context of the fiscal war. The topic is important, given that the RTD, despite appearing as the largest revenue waiver instrument in the State of Pará, has been the target of disputes regarding its ability to generate valid legal effects. To conclude this study, we sought to reveal the legal nature of the RTD, exposing its modalities that result in revenue waivers. It was argued that the RTD was used as an instrument of action and reaction in the context of the ICMS tax war. The work promoted the content exposition of the norms of the Financial Constitution, with the aim of extracting the constitutional regime of the State's financial activity, which imposes a series of requirements, limits and assumptions on the power to “detribute”. Having established the normative parameters of validity and control of tax benefits, we then set out to promote a diagnosis of the legality of the Differentiated Tax Regime, especially in the points relating to the requirements of the principle of specific legality, the dictates of the need for prior agreement interfederation of ICMS tax benefits, respect for what is also provided for by the State Constitution, and topics concerning the estimation of the amounts involved as a waiver of RTD revenue, its procedures, transparency and evaluation of results. By way of conclusion, weaknesses and inadequacies are identified in the creation, concession and management of RTDs, notwithstanding the recognition that there have been recent advances, with overcoming some legal problems, but persistence of others, which are subject to course correction . The research was based on the deductive method, with qualitative and exploratory research based on a bibliographical review and analysis of legal and administrative documents, especially procedures for creating RTDs whose access was possible via request for information.The work was also equipped with jurisprudential research, focusing on the decisions of the Federal Supreme Court concerning the matter.